Radionuclide bone SPECT/CT in the evaluation of knee pain: comparing two-phase bone scintigraphy, SPECT and SPECT/CT - Lu, Suat-Jin (Br J Radiol, 2018)
OBJECTIVE: To assess the role of single photon emission computed tomography (SPECT/CT) in the evaluation of knee pain as well as comparing bone scintigraphy (BS), SPECT and SPECT/CT, and assessing the incremental value of SPECT/CT. METHODS: BS, SPECT and SPECT/CT of patients with knee pain (39 patients, 65 knees, 105 lesions) were directly compared for lesion detection, localisation and characterisation using lesion-based, knee-based and patient-based analyses in this retrospective study. RESULTS: Lesion detection: BS (91.4%), SPECT (100%) and SPECT/CT (100%). SPECT and SPECT/CT detected significantly more lesions than BS (p < 0.05). Lesion localisation: BS (38.5–41.7%), SPECT (74.4–83.3%) and SPECT/CT (100%). SPECT localised significantly more lesions than BS; SPECT/CT localised significantly more lesions than BS and SPECT (p < 0.01). Lesion characterisation: BS (23.0–52.1%), SPECT (30.8–56.2%) and SPECT/CT (92.3–96.9%). SPECT/CT characterised significantly more lesions than BS and SPECT (p < 0.01). Characterisation of non-arthropathy lesions: BS (6.25%), SPECT (12.5%) and SPECT/CT (93.75%). SPECT/CT characterised significantly more non-arthropathy lesions than BS and SPECT (p < 0.01). BS and SPECT detected none, while SPECT/CT detected 100% of the causative/contributing/associated conditions that co-existed with osteoarthritis. Therefore SPECT/CT detected not only just osteoarthritis but also the causative/contributing/associated conditions. CONCLUSION: SPECT/CT added significant incremental value to BS and SPECT irrespective of whether evaluation was lesion-based, knee-based or patient-based. SPECT/CT represents a viable alternative to MRI, and addition of SPECT/CT to BS and SPECT should be considered in the evaluation of knee pain. ADVANCES IN KNOWLEDGE: Incremental value of bone SPECT/CT in knee pain.